Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan Perusahaan - Andreas Sebastian Sitompul; Elisabeth Magdalena Sitompul; Putri Melati Sitinjak; Melvin Sanro Jacobest Nainggolan; Rizki Christian Sipayung (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to determine the financial performance of PT Indofood Sukses Makmur Tbk for the 2020–2022 period based on financial ratio analysis. PT Indofood Sukses Makmur Tbk's financial performance can be measured using financial ratios consisting of Liquidity, Solvency, activity, and Profitability Ratios. The data analysis technique used in this study is a quantitative descriptive analysis technique, and the data used is secondary data in the form of the financial reports of PT Indofood Sukses Makmur Tbk for the 2020–2022 period obtained from the Official Website of the Indonesia Stock Exchange (IDX). The results showed that the liquidity ratio was relatively good, which could be seen from the value of the company's current ratio, quick ratio, and cash ratio. Even though the cash ratio value of PT Indofood Sukses Makmur Tbk is below 100% or 1, However, the value of the Current ratio, Quick ratio, and Cash Ratio of PT Indofood Sukses Makmur Tbk is so optimistic that it will increase every year. The solvevability Ratio of PT Indofood Sukses Makmur Tbk is classified as good because the debt-to-asset ratio (DAR) and debt-to-equity ratio (DER) values are optimistic that they will decrease, even though the DER value in 2020 and 2021 is above 100% or 1. PT Indofood's Activity Ratio Sukses Makmur Tbk is classified as good, as can be seen from the values of the Inventory Turnover Ratio, Fixed Asset Turnover Ratio, Total Asset Turnover Ratio, and Receivable Turnover Ratio, which have increased from 2020 to 2022. Although in 2022 the Inventory Turnover Ratio value will decrease due to excess inventory purchases, PT Indofood Sukses Makmur Tbk's Profitability Ratio is in a bad position, as can be seen from the proportions of PT Indofood Sukses Makmur Tbk's Net Profit Margin Ratio, Gross Profit Margin Ratio, Return on Assets (ROA), and Return on Equity (ROE) from 2021–2022, which experienced a significant decline. The percentage of impairment in 2021–2022 beats the proportion of increase in the ratio from 2020–2021.